Advancing Critico-Relational Inquiry: Is Tourism Studies Ready for a Relational Turn? - Pernecky, Tomas (Taylor and Francis Group, 2023)
This paper advances relational thought in tourism studies as a means for facilitating greater scrutiny of the relational matrices that have rendered possible the continuity of unjust, oppressive, and discriminatory relational patterns, particularly when these become detrimental to individuals, communities, other species, and the environment. Amid the growing determination to build more ethical, just, and sustainable futures, it contemplates whether critical scholarship has arrived at a relational turning point, whereby certain manifestations of tourism are increasingly deemed undesirable and problematic, and that transformation is needed in areas such as unsustainable growth, persistent colonial domination and racial conditioning, continued disregard for the environment, ongoing gender inequality and gender violence, and enduring injustices. The paper explains how relationality is interconnected with sustainability and critical scholarship and outlines the premise of critico-relational inquiry in the field. New conceptual vocabulary is offered to emphasise the critical vitality that can be injected into the examination of relations including: relational programming, relational reprogramming, relational hacking, meta-relational concerns, and relational thriving. Critico-relational inquiry is delineated as a viable strategy for transitioning towards sustainable alternatives, and as an integral part of future sustainability cum critical studies.
Keywords: 1503 Business and Management; 1506 Tourism; 1604 Human Geography; Sport, Leisure & Tourism; 3508 Tourism; 4406 Human geography